ALMA observations of Molecules in Supernova 1987A. Issue Volume 12:Issue S331(2017) (17th October 2017) - Matsuura, M.; Indebetouw, R.; Woosley, S.; Bujarrabal, V.; Abellán, F. J.; McCray, R.; Kamenetzky, J.; Fransson, C.; Barlow, M. J.; Gomez, H. L.; Cigan, P.; De Looze, I; et al.
Abstract: Supernova (SN) 1987A has provided a unique opportunity to study how SN ejecta evolve in 30 years time scale. We report our ALMA spectral observations of SN 1987A, taken in 2014, 2015 and 2016, with detections of CO, 28 SiO, HCO + and SO, with weaker lines of 29 SiO. We find a dip in the SiO line profiles, suggesting that the ejecta morphology is likely elongated. The difference of the CO and SiO line profiles is consistent with hydrodynamic simulations, which show that Rayleigh-Taylor instabilities causes mixing of gas, with heavier elements much more disturbed, making more elongated structure. Using 28 SiO and its isotopologues, Si isotope ratios were estimated for the first time in SN 1987A. The estimated ratios appear to be consistent with theoretical predictions of inefficient formation of neutron rich atoms at lower metallicity, such as observed in the Large Magellanic Cloud (about half a solar metallicity). The deduced large HCO + mass and small SiS mass, which are inconsistent to the predictions of chemical model, might be explained by some mixing of elements immediately after the explosion. The mixing might have made some hydrogen from the envelope to sink into carbon and oxygen-rich zone during early days after the explosion, enabling the formation of a substantial mass of HCO + . Oxygen atoms may penetrate into silicon and sulphur zone, suppressing formation of SiS. Our ALMA observations open up a new window to investigate chemistry, dynamics and explosive-nucleosynthesis in supernovae.